A Conceptual Model of Teaching Applied Engineering Subjects - Bhattacharya, B. K. (Journal of Engineering Education Transformations, 1994)
This paper presents a conceptual model of teaching, where emphasis is on developing problem solving abilities in students rather than on covering the syllabus by the teacher. It also shows a direction as to how to correlate effective curriculum implementation with the teacher development progrmmes including preparation of teaching-learning material.